Knocking at The Door: An Exploratory Field Study of Cadre Membership from the Leader’s Perspective (Journal of Organizational Psychology, 2019)
This study addresses an often-overlooked question in LMX research: What signals to a dyadic leader that one subordinate should be extended an exchange opportunity that may ultimately result in a unique strategic alliance while others are not extended such an offer? Conducted in a field setting, this exploratory study involved executives and upper level management of 17 firms in a Midwestern metropolis. Data secured from a sample of 155 matched dyadic pairs suggests that subordinate attractiveness appears predictable beyond random chance by the leader’s subjective assessment of the subordinate’s cognitive ability, veracity, and, to a much lesser degree, the subordinate’s extra-role behavior.
Keywords: Organizational Psychology; Leadership; LMX research; subordinate’s extra-role behavior; Cadre Membership